2018
DOI: 10.1371/journal.pone.0203289
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic dose distribution from interfractional motion in carbon ion radiation therapy for prostate cancer shows rectum sparing with moderate target coverage degradation

Abstract: PurposeThis observational study investigates the influence of interfractional motion on clinical target volume (CTV) coverage, planning target volume (PTV) margins, and rectum tissue sparing in carbon ion radiation therapy (CIRT). It reports dose coverage to target structures and organs at risk in the presence of interfractional motion, investigates rectal tissue sparing, and provides recommendations for lowering the rate of toxicity. We also propose probabilistic DVH based on cone-beam computed tomography (CB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The possibility that gastrointestinal cancers may benefit from CIRT also looks promising [61]. Patients with prostate cancer treated with CIRT showed better outcomes than those treated with conventional RT [62,63]. It is increasingly assumed that accelerated carbon ions may be a better treatment option than conventional RT for deep-seated, radioresistant, and hypoxic tumors [60].…”
Section: Proton Therapymentioning
confidence: 99%
“…The possibility that gastrointestinal cancers may benefit from CIRT also looks promising [61]. Patients with prostate cancer treated with CIRT showed better outcomes than those treated with conventional RT [62,63]. It is increasingly assumed that accelerated carbon ions may be a better treatment option than conventional RT for deep-seated, radioresistant, and hypoxic tumors [60].…”
Section: Proton Therapymentioning
confidence: 99%
“…Using the measured data, dose reduction and the region caused by fiducial markers, dose-volume histograms of a target, inside which the markers were set at (a) proximal, (b) center and (c) distal depth, are simulated study (Figure 5) was comparable with that reported previously. [26][27][28] The margins of bsPTV and PTV evl were decided as shown in Table 1. There is still room to improve these margins.…”
Section: Discussionmentioning
confidence: 99%
“…reported that use of various immobilization tools showed no significant difference in overall prostate movements, and the amount of interfractional and intrafractional prostate motion in the present study (Figure 5 ) was comparable with that reported previously. 26 , 27 , 28 …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, once-a-week imaging protocol has been adopted by many centers worldwide (10) including our hospital. However, the unknown anatomic and positioning deviations of the remaining fractions may induce unacceptable target under-dose (11,12) and potential tumor recurrence (13). Existing studies of imaging frequencies focused more on geometric impact (14)(15)(16)(17), yet analysis based on dose accumulation is missing but clinically desirable.…”
Section: Introductionmentioning
confidence: 99%